2020
DOI: 10.1093/gerona/glaa298
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation in the Gestational Phase of Female Rats Improves Age-Related Memory Impairment and Neuroinflammation in Their Adult and Aged Offspring

Abstract: Folic acid (FA) supplementation is important during pregnancy to avoid malformations in the offspring. However, it is unknown if it can affect the offspring throughout their lives. To evaluate the offspring, female mother rats (Dam’s) were separated into 5 groups: Four groups received the AIN-93 diet, divided into control and FA (5, 10 and 50 mg/kg), and an additional group received a FA deficient diet, the diet was performed during pregnancy and lactation. We evaluated the female offspring of these Dam’s (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For instance, folic acid reduces hippocampal myeloperoxidase activity to alleviate neuroinflammation and improve memory impairment in sepsis‐induced rats 28 . Another in vitro study indicated that lipopolysaccharide‐activated microglia respond less inflammatory to folic acid because it inhibits the activation of NF‐kB and JNK and upregulates p38 MAPK phosphorylation 4 . Besides, our previous work has shown that FD enhanced microglia immune responses via the Notch1/nuclear factor kappa B p65 pathway to increase brain injury 8 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…For instance, folic acid reduces hippocampal myeloperoxidase activity to alleviate neuroinflammation and improve memory impairment in sepsis‐induced rats 28 . Another in vitro study indicated that lipopolysaccharide‐activated microglia respond less inflammatory to folic acid because it inhibits the activation of NF‐kB and JNK and upregulates p38 MAPK phosphorylation 4 . Besides, our previous work has shown that FD enhanced microglia immune responses via the Notch1/nuclear factor kappa B p65 pathway to increase brain injury 8 .…”
Section: Discussionmentioning
confidence: 98%
“… 28 Another in vitro study indicated that lipopolysaccharide‐activated microglia respond less inflammatory to folic acid because it inhibits the activation of NF‐kB and JNK and upregulates p38 MAPK phosphorylation. 4 Besides, our previous work has shown that FD enhanced microglia immune responses via the Notch1/nuclear factor kappa B p65 pathway to increase brain injury. 8 The current study investigated the effect of FD on the astrocytes under ischemia‐reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats in the VEH groups were given an equivalent volume of vehicle. The folate dose was based on prior preclinical work that indicated that doses between 10 and 50 mg/kg ameliorated oxidative stress and inflammatory processes (Garcez et al., 2021). We also recently reported that EtOH exposure (2.0 g/kg/day) on GDs 17–20 induced hyperactivity and anxiety and increased EtOH intake in offspring.…”
Section: Methodsmentioning
confidence: 99%